Maritime operations law in practice : key cases and incidents - Letts, David; McLaughlin, Rob (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"The law that applies to maritime operations at sea is complex and comprises two distinct elements, treaty law 1982 UN Convention on the Law of the Sea, and the cases and incidents that occur at sea in both peacetime, and during armed conflict, which result in the creation of customary international law applicable to maritime operations at sea. Covering sovereignty and vessel status, jurisdiction and interdiction, freedom of navigation, maritime law enforcement and security, and the law of naval warfare, this edited collection brings together the most famous and influential cases and incidents at sea. Exploring the entire spectrum of maritime operations from high end warfighting to constabulary operations that are conducted by naval forces and maritime law enforcement agencies at sea to provide the factual circumstances of each case or incident. Offering sophisticated analysis and insights into the case or incidents enduring importance, and their significance for the development of the law applicable to maritime operations. Offering a detailed account and evaluation of the most critical but rarely understood cases in Maritime Operations Law, which encourages comparison between key cases, this book will be an essential reference for practitioners, scholars, teachers, and students of maritime operations law"--
1 Introduction / David Letts Rob McLaughlin -- Part I: Sovereignity and vessel status. 2 The Lotus Case (France v Turkey) / Camille Goodman -- 3 ARA Libertad: refining the legal grounds for warship-immunity in foreign ports / Martin Fink -- Part II: Jurisdiction and interdiction. 4 The MS Achille Lauro Hijacking / Steven Haines -- 5 The So San Incident / Douglas Guilfoyle -- 6 United States of America v Lei Shi / David Letts -- 7 The Ali and Shibin Cases in Relation to Article 101(C) of UNCLOS and the Facilitation of Piracy / Tamsin Phillipa Paige Rob McLaughlin -- Part III: Freedom of navigation, maritime law enforcement, and maritime security. 8 The Black Sea Bumping Incident / Raul (Pete) Pedrozo -- 9 I'm Alone / Stuart Kaye -- 10 The Red Crusader Incident / Rob McLaughlin -- 11 The MV Saiga (No.2) case: St Vincent and the Grenadines v Guinea / Phil Drew -- 12 The 'Whiskey on the Rocks' Incident / Cameron Moore -- Part IV: Law of Naval warfare. 13 RMS Lusitania / Cameron Moore -- 14 The Admiral Graf Spee in Montevideo / James Farrant -- 15 The Altmark Incident / James Farrant -- 16 The Sinking of ARA General Belgrano / David Letts -- 17 The Mavi Marmara Incident / Douglas Guilfoyle.
Keywords: Law of the sea; War, Maritime (International law); Maritime law -- Criminal provisions; LAW / General; LAW / International; LAW / Maritime